THE EFFECTIVENESS OF MATHEMATICS LEARNING BASED ON OPEN-ENDED WITH PROBLEM BASED LEARNING METHOD ON CREATIVE THINKING ABILITY - Khusnul Khotimah; Suparyan Suparyan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Learning tends to be dominated by teachers, which causes some students to be passive in learning. This is thought to make the level of students' creative thinking skills low. This study aims to determine whether there are differences in the level of creative thinking abilities of students who use Open-ended based learning with Problem Based Learning (PBL) methods with those using Conventional learning methods for students' creative thinking skills of VIII Grande students of State Junior High School (SMP Negeri) 2 Majenang Cilacap Regency At Odd Semester In Academic Year of 2018/2019. The population in this study there are eight classes. The sample was taken by two classes with a random sampling technique for the class and selected VIII-G class as the control class and VIII-H as the experimental class. The design in this study is the Pretest-Posttest Control Group design. Data collection techniques using test techniques (pretest and posttest) and questionnaire techniques. Data collection instruments in the form of tests and test questionnaires. Test data collection instruments using validity, discriminating power, and reliability tests. Data analysis techniques using analysis prerequisite tests include normality test, homogeneity test, and hypothesis testing using the t-test. The study results at a significant level of 5%, and df = 61 indicate that: (1) there is a difference in the value of posttest mathematics using open-ended-based learning with problem-based learning (PBL) method with learning using conventional methods. This is indicated by ttable = t (0,025) (61) = 1,996 and tcount = 2,988762 which means ttable< tcount(2) Learning using Open-ended PBL method is more effective than learning using conventional methods. This is indicated by the value of tcount = 2.988762 and ttable = t (0.025) (61) = 1.670385 which means tcount>ttable .